Information System for Predicting the Technical Condition of Electrical Equipment Devices - Ermakova, D. A.; Fateev, V. A. (BIO web of conferences, 2023)
The information system for predicting the technical condition of electrical equipment devices was described, which allows to analyze the data obtained and predict the residual life at the output in the form of regulatory documents. A new database using the open-source relational database management system MySQL (hereinafter – RDBMS MySQL) was designed. An analysis of the subject area and an analysis of the operation of electrical equipment devices was carried out. The developed information system allows to analyze the data obtained and predict the residual life in the form of regulatory documents.